Priority-aware optical shared protection coupled with mutation probability - Fawaz, Wissam (2017)
The next big challenge for optical network operators is to meet the diverse availability requirements of the various subscribed services through the adoption of appropriate protection strategies. One promising scheme that has been proposed in the open literature and that is presenting itself as a potential approach to dealing with this challenge is the priority-aware protection scheme. However, the priority-aware protection strategy suffers from a major limitation as it privileges the failed high priority connections taking no account of the failed low priority ones. As such, this paper proposes to combine priority-aware shared protection with a parameter called mutation probability thus giving birth to a more effective protection strategy. The mutation probability parameter expresses the likelihood that a low-priority connection be promoted temporarily to a higher priority level during its recovery. The proposed mutation-based protection strategy therefore allows optical operators to improve the availability of their low-priority clients without violating the availability requirements of their high-priority ones. Performance of this novel protection strategy is analyzed in this paper by precisely calculating the connection unavailability that results from its deployment. A computational framework is proposed in this regard to highlight the merit that the mutation-based protection strategy has over the existing priority-aware protection scheme